Engineering Injectable Anti‐Inflammatory Hydrogels to Treat Acute Myocardial Infarction. Issue 7 (27th April 2022) - Zhang, Xiaoping; Liu, Wenguang
Abstract : Acute myocardial infarction (AMI) poses serious threats to human health. Suppressing long‐term inflammation is a promising strategy to improve cardiac function following AMI. However, the direct injection of anti‐inflammatory drugs after AMI can trigger adverse events due to systemic off‐target effects and bioavailability issues. Injectable hydrogels can be used for local transportation of various therapeutic molecules through minimally invasive technology to overcome the side effects of intravenous injection. Herein, the anti‐inflammatory mechanisms and applications of injectable hydrogels are reviewed to deliver anti‐inflammatory drugs, antioxidants, immune‐regulation drugs, stem cells and their derived exosomes, and therapeutic gas to reduce the inflammatory response to treat AMI. The outlook on challenges in the design of hydrogels for treating AMI is also presented. Abstract : Inflammation is widely involved in the pathological process of acute myocardial infarction (AMI). This article introduces the anti‐inflammatory mechanisms and applications of injectable hydrogels to deliver anti‐inflammatory drugs, antioxidants, immune‐regulation drugs, stem cells and their derived exosomes, and therapeutic gas to reduce the inflammatory response to treat AMI.